Isolation, identification, biological characteristics analysis, and inactivated vaccine research of Mycoplasma canis from respiratory tract of dogs in Yunnan Province, China - Kou, Meiling; Xu, Tao; Wang, Yinan; Xie, Jiarui; Huang, Jiangyan; Xin, Yun; Chen, Chao; Fan, Qing; Mao, Aiguo; Miao, Haisheng (Frontiers in Veterinary Science, 2025)
IntroductionResearch on Mycoplasma canis remains limited, possibly because dogs in most regions are usually not raised on a large scale or in intensive farming. Furthermore, existing antibacterial drugs are often proven to be effective in inhibiting or eradicating M. canis, resulting in insufficient attention being paid to its pathogenic potential. However, with the widespread use of antibacterial drugs, an increase in drug resistance has been found in human mycoplasma pneumoniae, bovine mycoplasma and avian mycoplasma also faces similar challenges. Given the irreplaceable role of dogs as companion animals and work partners, it is crucial to enhance research on Mycoplasma canine, especially in the areas of epidemiology, diagnostic techniques, drug resistance mechanisms and vaccine development. This study found that M. canis inoculated into liquid Pleuropneumonia-Like Organisms (PPLO) medium at 37 °C could reach the growth peak within 24 h and maintain this level for approximately 24 h. The survival rate is higher in environments with PH values of 6.5, 7.0 and 7.5 respectively, and it is suitable for storage in neutral or weakly acidic environments. 5 mM of BEI inactivated agent can completely inactivate M. canis within 15 h, and the experimental dogs produced specific antibodies within 1 week after vaccination with the inactivated vaccine, with a positive rate of 100%. It provides a theoretical basis and experimental evidence for the subsequent in-depth exploration of the pathogenic mechanism of M. canis and the development of its vaccine.MethodsResearchers collected eight lung tissue samples from working dogs exhibiting typical respiratory symptoms in Kunming City, Yunnan Province. From these samples, one strain of canine mycoplasma was successfully isolated. To characterize this isolate comprehensively, a series of technical approaches were employed. The growth dynamics of the mycoplasma strain were assessed by monitoring color changes in the culture medium. Molecular identification was conducted using polymerase chain reaction (PCR). Additionally, preliminary studies were undertaken regarding its biological characteristics and the development of an inactivated vaccine; these efforts provide both theoretical foundations and experimental support for future investigations into the pathogenic mechanisms and vaccine development for M. canis.ResultsThe findings indicated that M. canis could grow stably within PPLO medium and was confirmed as belonging to the M. canis genotype through 16S rRNA gene sequence analysis. The freshly cultivated strain was inoculated into liquid PPLO medium at a concentration rate of 1%. It reached its peak growth within 24 h at 37 °C and maintained this level for approximately another 24 h. Subsequently, the number of viable bacteria gradually declined. In environments with pH values of 6.5, 7.0, and 7.5 respectively, the survival rate of viable bacteria was significantly higher than that observed at pH 8.0. Therefore, it is recommended that the M. canis strain preserved for seed use be maintained in a neutral or weakly acidic environment. Additionally, the BEI inactivating agent at a final concentration of 5 mM can completely inactivate the strain within 15 h. Four experimental dogs developed specific antibodies within 1 week after being vaccinated with the inactivated vaccine, achieving a positive rate of 100%, which preliminarily confirms that the vaccine elicits an immune response.ConclusionThis study successfully isolated and identified M. canis, investigated its growth characteristics in PPLO medium, and established a method for preparing inactivated vaccines along with preliminary evaluations thereof. These findings provide a foundation for further research into the infection dynamics and pathogenicity of M. canis while offering valuable insights for preventing and controlling M. canis infections.